Work Absenteeism and Presenteeism Loss in Patients With Non-Cardiac Chest Pain. Issue 9 (September 2018) - Félin-Germain, Alix; Denis, Isabelle; Turcotte, Stéphane; Fleet, Richard; Archambault, Patrick; Dionne, Clermont E.; Foldes-Busque, Guillaume
Abstract : Objective: To assess work absenteeism and presenteeism, and to identify biopsychosocial predictors of these outcomes in workers with non-cardiac chest pain (NCCP). Methods: This retrospective cohort study included 375 active workers consulting in an emergency room for NCCP. Results: About 66% (247/375) of participants reported work absenteeism in the 3 months preceding the consultation, while 36% (134/375) reported presenteeism during the same period. A family income >$29, 999, and reporting at least a mild impact of chest pain on family functioning, social functioning, or physical activities, were associated with work absenteeism. Presenteeism was associated with younger age, symptoms of depression, and heart-focused anxiety. Conclusions: Work absenteeism and presenteeism are highly prevalent among patients with NCCP. Family income and impacts of NCCP on functioning, are associated with increased occupational burden in these patients. Abstract : Supplemental Digital Content is available in the text